Deteksi Dini Anemia Pada Remaja Di RT 19 Kelurahan Sawah Lebar Baru Kota Bengkulu Oleh Mahasiswa KKN S1 Kebidanan Universitas Bengkulu - Atika Salma; Suryani, Irma Ade; Putri, Anisa Ika (Utami Publisher, 2025)
Anemia in adolescents is a significant health problem in indonesia, with a high prevalence among young girls. this activity aims to conduct early detection of anemia in adolescents in rt 19, sawah lebar baru village, bengkulu city, through hemoglobin (hb) level examinations and education on anemia prevention. the methods used include health education (delivering material about anemia, its causes, symptoms, and prevention), anemia screening (simple physical examinations such as checking conjunctiva and palms, and hemoglobin measurement using a digital hb meter), as well as nutrition education and iron supplementation. the results showed an increase in participants' knowledge about anemia and a reduction in anemia prevalence after the intervention.